The Economic Benefits of a Major Canadian Forestry Contribution Program for Indigenous Peoples - Kuhnke, Dieter; Cahill, Ian (Journal of Aboriginal Economic Development, 2024)
This paper evaluates whether the First Nations Forestry Program (FNFP), a contribution program for Indigenous Peoples in Canada, had a statistically measurable effect on the well-being of participating reserves’ inhabitants. Funding data from 1,078 projects was paired with reserve inhabitant profiles from two Statistics Canada censuses. Multiple regression models were then used to test for the statistical significance of project-funding treatments. The results suggest that from 2006 to 2010, the FNFP significantly affected the after-tax incomes of reserve inhabitants who had worked in forestry, as well as a lesser effect on the after-tax incomes of reserve families.